The Effectiveness of Job Stress Management on Improving Mental Health and Self-Efficacy of Training the Teachers - Habibi, Mojtaba; Birashk, Behroz; Ashoori, Ahmad; Pooravari, Minoo; Salehi, Somaieh (International Journal of Applied Behavioral Sciences, 2017)
Background: Job stress is one of the most important problems in the modern world and have created many concerns for many organizations. The aim of present study was to determine the effectiveness of job stress management on improving mental health and self-efficacy of training the teachers.Methods: Forty teachers(21 women, and 19 men) were selected by simple random sampling assigned into the experimental and control groups. With a pre-test and post-test-control group design, subjects in the experimental group, undergone sessions of stress management training both groups were evaluated using Teachers’ Sense of Efficacy Scale(TSES) and mental health inventory(MHI) in pre-test and post-test. Data analyzed by descriptive statistics and Multivariate analysis of covariance (MANCOVA). Results: Findings show that there were not significant differences between two groups in pretest, but stress management training, significantly increases psychological well-being and teaching self-efficacy scores in experimental group.Conclusion: The stress management training, could be intervention program in target groups and counseling centers, and with enhancing psychological well-being and senses of teaching self-efficacy of teachers, increase education to productivity of schools.